The role of PET/CT in cervical cancer - Herrera, Fernanda G.; Prior, John O. (Frontiers in Oncology, 2013)
In locally advanced cervical cancer, 18F-fluorodeoxyglucose (FDG) PET/CT has become important in the initial evaluation of disease extent. It is superior to other imaging modalities for lymph node status and distant metastasis. PET-defined cervical tumour volume predicts progression-free and overall survival. Higher FDG uptake in both primary and regional lymph nodes is strongly predictive of worse outcome. FDG PET is useful for assessing treatment response three months after completing concurrent chemo-radiotherapy (CRT) and predicting long-term survival, and in suspected disease recurrence. In the era of image-guided adaptive radiotherapy, accurately defining disease areas is critical to avoid irradiating normal tissue. Based on additional information provided by FDG PET, radiation treatment volumes can be modified and higher doses to FDG-positive lymph nodes safely delivered. FDG PET/CT has been used for image-guided brachytherapy of FDG-avid tumour volume, while respecting low doses to bladder and rectum. Despite survival improvements due to CRT in cervical cancer, disease recurrences continue to be a major problem. Biological rationale exists for combining novel non-cytotoxic agents with CRT, and drugs targeting specific molecular pathways are under clinical development. The integration of these targeted therapies in clinical trials, and the need for accurate predictors of radio-curability is essential. New molecular imaging tracers may help identifying more aggressive tumours. 64Cu-labeled dyacetyl-di(N(4)-methylthiosemicarbazone) (64Cu-ATSM) is taken up by hypoxic tissues, which may be valuable for prognostication and radiation treatment planning. PET/CT imaging with novel radiopharmaceuticals could further impact cervical cancer treatment as surrogate markers of drug activity at the tumour microenvironment level. The present article reviews the current and emerging role of PET/CT in the management of cervical cancer.